Aphasia Severity in Chronic Stroke Patients: A Combined Disconnection in the Dorsal and Ventral Language Pathways. (March 2015) - Rosso, Charlotte; Vargas, Patricia; Valabregue, Romain; Arbizu, Céline; Henry-Amar, François; Leger, Anne; Lehéricy, Stéphane; Samson, Yves
Background . The contribution of lesion size and location in poststroke aphasia is debated, especially the extent to which aphasia severity is affected by damage to specific white matter areas. Objective . To identify specific white matter areas critical for poststroke aphasia global severity and to determine whether injury to these areas had more impact on aphasia severity than the infarct volume. Methods . Twenty-three chronic poststroke aphasic patients were assessed with the Aphasia Rapid Test (ART) and the Boston Diagnosis Aphasia Examination (BDAE) global severity scales and underwent diffusion tensor and structural imaging. Voxel-based diffusion tensor imaging regression analysis was used to determine in which areas fractional anisotropy (FA) abnormalities were correlated with ART and BDAE severity scales. The relationships between aphasia severity, FA values, and infarct volumes were investigated using global and partial correlations. Results . We found a critical area associated with aphasia severity overlapping with the arcuate and the inferior fronto-occipital fasciculi, resulting in a combined disconnection of the dorsal and ventral pathways. ART scores were inversely correlated with FA values in this region, with greater severity present with lower FA values (correlation coefficient = −0.833, P < .0001). The proportion of variance explained by the FA value was higher than the proportion of variance explained by the infarct volume ( R 2 = 68% vs 27%, P = .01). The impact of infarct volume on aphasia severity disappeared when damage to this critical white matter area was taken into account ( P = .38). Conclusion . The assessment of the integrity of this region may potentially have a clinical impact in neurorehabilitation and acute decision making.